2021
DOI: 10.4252/wjsc.v13.i11.1747
|View full text |Cite
|
Sign up to set email alerts
|

Application of adipose-derived stem cells in treating fibrosis

Abstract: Fibrosis is the hyperactivation of fibroblasts that results in excessive accumulation of extracellular matrix, which is involved in numerous pathological changes and diseases. Adipose-derived stem cells (ASCs) are promising seed cells for regenerative medicine due to their bountiful source, low immunogenicity and lack of ethical issues. Their anti-fibrosis, immunomodulation, angiogenesis and other therapeutic effects have made them suitable for treating fibrosis-related diseases. Here, we review the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…On day 14 after implantation, the harvested tissues from the two ADSC-laden groups showed a well-organized epidermal structure and a well-distributed dermal structure with clear vascular and fibrous tissues and minimal inflammatory cell infiltration. We speculate that the limited inflammatory infiltration may be related to modulation of neutrophil, macrophage, and lymphocyte responses by MSC-secreted growth factors and cytokines [ 53 ] . In comparison, the epidermis was fractured in samples from the two groups treated with acellular scaffolds, and fibrous tissue hyperplasia was found in the dermis, especially in the GelMA–HAMA group.…”
Section: Resultsmentioning
confidence: 99%
“…On day 14 after implantation, the harvested tissues from the two ADSC-laden groups showed a well-organized epidermal structure and a well-distributed dermal structure with clear vascular and fibrous tissues and minimal inflammatory cell infiltration. We speculate that the limited inflammatory infiltration may be related to modulation of neutrophil, macrophage, and lymphocyte responses by MSC-secreted growth factors and cytokines [ 53 ] . In comparison, the epidermis was fractured in samples from the two groups treated with acellular scaffolds, and fibrous tissue hyperplasia was found in the dermis, especially in the GelMA–HAMA group.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, N-cadherin-transfected ASCs promote angiogenesis and cardiomyocyte differentiation, thereby reducing ventricular fibrosis and increasing the ejection fraction in a mouse model of ischemic heart disease [ 38 ]. Anti-fibrotic effects of ASCs have been repeatedly reported in the lungs, kidneys, and skin [ 17 , 18 , 39 ]. Based on these studies, inhibition of the TGFβ/Smad signaling axis, paracrine effects by various growth factors released from ASCs, anti-oxidative effects, and anti-inflammatory effects have been suggested as mechanisms by which ASCs suppress fibrosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-fibrotic effects of ASCs have been repeatedly reported in the lungs, kidneys, and skin [ 17 , 18 , 39 ]. Based on these studies, inhibition of the TGFβ/Smad signaling axis, paracrine effects by various growth factors released from ASCs, anti-oxidative effects, and anti-inflammatory effects have been suggested as mechanisms by which ASCs suppress fibrosis [ 39 ]. In this study, we found that the mRNA levels of TGFβ, a master regulator of fibrosis that governs the production of extracellular matrix, and molecules operating downstream of TGFβ, were decreased in ASC-treated peri-implant capsules.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are no previous reports on short exposition (4h) of cells in vitro to TGF-β1, others tried concentrations from 0.1 to 10 ng/ml for longer periods (24h; Li et al. 2021 ; Qin et al. 2023 ).…”
Section: Introductionmentioning
confidence: 99%